Reconstruction of Employment Termination Regulations in Indonesia Following the Job Creation Law: A Comparative Study with South Korea - Helwan Kasra; Slamet Riyanto; Dea Justicia Ardha (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to analyse the regulation of termination of employment in Indonesia following the enactment of Law No. 6 of 2023 on Job Creation, compare it with the legal framework in South Korea, and propose a reconstructed model that ensures a more balanced and equitable employment termination system. Termination of employment (PHK) remains a central issue in labour law because it directly affects workers’ rights, the stability of industrial relations, and sustainable economic development. The enactment of Law No. 6 of 2023 on Job Creation has introduced significant changes to Indonesia’s employment termination framework, reflecting a shift toward greater labour market flexibility while raising concerns regarding legal certainty and the adequacy of worker protection. This study employs normative legal research using statutory and comparative law approaches through an analysis of legislation, judicial decisions, and relevant scholarly literature. The findings reveal that Indonesia’s current regulatory framework primarily focuses on post-termination compensation, while providing insufficient safeguards regarding substantive grounds for dismissal and preventive procedural protections. In contrast, South Korea adopts the principle of dismissal for just cause, supported by strict and participatory dismissal procedures, comprehensive unemployment insurance, and active labour market policies. Based on this comparative analysis, the article proposes a reconstructed model for Indonesia that incorporates clear limitations on dismissal based on valid and objective grounds, strengthens preventive and transparent dismissal procedures, and expands comprehensive post-termination social protection. The proposed model is expected to achieve a more balanced relationship between labour market flexibility and worker protection while enhancing legal certainty and fairness within Indonesia’s industrial relations system.